Social identity and deinstitutionalisation: a study about a neighborhood that receives therapeutic residences in Brazil - Ribeiro Neto, Pedro Machado; Avellar, Luziane Zacché (Saúde e Sociedade, 2015)
Therapeutic Residences (TRs) are important devices for mental health care. However, the communities' resistance imposes a challenge to their implementation. In order to analyze this reality, this study discusses the social conceptions of co-inhabiting with TRs from the perspective of residents of a residential complex that receives thee TRs. Under an ethnographic light, interviews and observations were conducted. The TRs were represented as safe places, exerting control over their residents, and playing the role of a psychiatric hospital. Furthermore, the presence of the TRs in that neighborhood allowed them to be called groups of crazies by the outside people, which endangered the social identity of the TR residents. A tendency of intergroup differentiation was observed in the relationship between residents of the neighborhood and of the TRs, which can be understood as a necessity of the social identity process. Old signs associated with madness were observed among the neighborhood residents, but they were undone by the daily contact with the TR residents, which is a positive aspect to emphasize. Even with the separation tendencies from the TRs, as observed in this study, a movement based on the actual experience of living in the same neighborhood as the TRs exists and points to the possibility of coexistence without major conflicts between the groups involved. This illustrates the ambiguity of the relationships and the need for further research, since there's no recipe for this cake as people may think in the context of living near TRs.